Cross-site scripting (xss) vulnerability in the cirebon district health service web system - Isma Elan Maulani; Siti Ainul Kholipah; Mamduh Rihadatul Aisy (Jurnal Indonesia Sosial Teknologi, 2024)
In an era of rapid growth in information technology, the enormous benefits generated are also accompanied by significant security risks. This research was conducted by an independent security researcher, Isma Elan Maulani, to identify and analyze security vulnerabilities on the Cirebon District Health Service website. The focus of the research centered on the "Search" page, where the main finding was the presence of a Cross-Site Scripting (XSS) vulnerability. XSS opens up the potential for attackers to insert and execute JavaScript scripts within web pages, threatening the security and integrity of data. Tests involving custom input successfully proved that JavaScript scripts could be executed without any sanitization or protection. These findings show the urgency to improve the security of the Cirebon District Health Service website. Recommended remedial steps involve implementing effective input sanitation, more rigorous validation of user input data, and implementing stricter security policies. Collaboration with authorities and cybersecurity researchers is recommended to gain additional insights and more comprehensive solutions. Digital security is not only the responsibility of developers, but also a collective obligation to create a safer and more secure online environment for all users.